Enterprise risk management and firm performance: Empirical evidence from Ghana equity market - Sylvester Senyo Horvey; Jacob Ankamah (Cogent Economics & Finance, 2020)
This paper examines the linear and non-linear relationship between Enterprise Risk Management (ERM) and firm performance while focusing on how operational status (financial and non-financial listed firms' status) affects this relationship in Ghana. Analysis of 30 listed firms on Ghana Stock Exchange between 2010 and 2016 in a robust fixed effect and random effect estimation techniques, presented new insights into ERM literature. We showed that ERM propels firm performance at both the firm level (return on assets and equity) and market level (Tobin Q) performance of listed firms in Ghana. A non-linear inverted U-shape is observed when return on equity is employed as a performance indicator while a non-linear direct U-shape is observed when return on assets and Tobin Q are employed as performance indicators. A non-linear relationship exists between ERM and performance of listed firms in Ghana whether the non-linearity is an inverted U shape or direct U shape depends on the firm performance. This paper recommends that firms should implement fundamental robust measures and dynamic risk management techniques to get better ERM outcome. Enterprise Risk Management should be implemented in both financial firms and non-financial firms because firms which practice ERM are more likely to perform better than Non-ERM counterparts.
Keywords: 330; Enterprise risk management; firm performance; Ghana; Tobin Q